The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.trsl.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulated copper/zinc superoxide dismutase exerts differential effects on glucose vs lipid homeostasis depending on the diet composition possibly via altered AMPK signaling

Abstract: Evidence suggests that superoxide dismutase 1 (SOD1) promotes glucose versus lipid metabolism depending on the diet type. We recently reported that nanoformulated SOD1 (Nano) improved lipid metabolism without altering glucose homeostasis in high fat (HF) diet-fed mice. Here, we sought to determine the effects and potential mechanisms of Nano in modulating glucose and lipid homeostasis in mice fed a normal chow diet (CD) versus HF diet. Mice were fed a CD or a HF diet (45%) for 10 wk and injected with Nano once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…A cross-sectional study showed that serum SOD level negatively correlates with BMI, TG, BG, and carotid artery intima-media thickness [46], in accordance with the present study. Perriotte-Olson et al found that mice fed a high-fat diet and treated with nanoformulated SOD (NanoSOD) showed significant decreases in plasma and liver TG levels [47], and improved glucose and lipid metabolism [48]. The evidence above indicates that SOD plays an important role in glucose and lipid metabolism, and the mechanism of its effect requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study showed that serum SOD level negatively correlates with BMI, TG, BG, and carotid artery intima-media thickness [46], in accordance with the present study. Perriotte-Olson et al found that mice fed a high-fat diet and treated with nanoformulated SOD (NanoSOD) showed significant decreases in plasma and liver TG levels [47], and improved glucose and lipid metabolism [48]. The evidence above indicates that SOD plays an important role in glucose and lipid metabolism, and the mechanism of its effect requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…DMEM, 500 ng mL −1 of BDNF, Nano-BDNF ( Z −/+ = 946), or equivalent amount of PEG-PLE polymer in the Nano-BDNF formulation were incubated with the cells for 5 min at 37 °C in serum-free DMEM then moved to ice for 20 min and lysed using radioimmunoprecipitation assay buffer with proteinase and phosphatase inhibitors. Western blot analysis was conducted as reported previously [41] with modifications. Briefly, 10 μg total protein from the cell lysates was loaded in each well of 7.5% Mini-PROTEAN® TGX™ precast gels and run at 150 V for 1 h. Proteins were then transferred to 0.45 μm polyvinylidene difluoride membranes at 500 mA current for 1 h. The membranes were then blocked in either 5% BSA (for detection of phosphorylated TrkB and ERK) or 5% nonfat dry milk (for detection of total TrkB and ERK) for 30 min at RT followed by an overnight incubation at 4 °C with primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…once every two days for 15 days). In particular, SOD administration reduced the levels of serum triglycerides [ 225 ]. The same formulation reduced the macrophage and inflammatory markers in visceral adipose tissue and the originating stromal cells [ 226 ].…”
Section: Sod As a Pharmacological Agentmentioning
confidence: 99%